Optimization and dynamic responses of an integrated fuel cell and battery system for an 800 kW ferry: A case study. (November 2022) - Pourrahmani, Hossein; Gay, Martin; Yavarinasab, Adel; Van herle, Jan
Abstract: The recent targets by different countries to stop the sales or registrations of internal combustion engines (ICE) have led to the further development of battery and fuel cell technologies to provide power for different applications. The main aim of this study is to evaluate the possibility of using an integrated Lithium-Ion battery and proton exchange membrane fuel cell (PEMFC) as the prime mover for a case study of a 800 kW ferry with a total length of 50.8 m to transport 780 passengers for a distance of 24 km in 70 min. Accounting for five types of Lithium-Ion batteries and different numbers of PEMFCs, twenty-five scenarios are suggested based on a quasi-static model. To perform the optimization, the Performance Criterion of the Fuel cell–Battery integrated systems (PCFB) is introduced to include the effects of the sizes, weights, costs, hydrogen consumption, efficiency, and power in addition to the number of fuel cells and the battery capacity. Results indicate that the maximum PCFB value of 10.755 ( 1 / kg 2 m 3 $ ) can be obtained once the overall size, weight, efficiency, hydrogen consumption, and cost of the system are 18 m 3, 11160 kg, 49.25%, 33.6 kg, and 119.58 k$, respectively, using the Lithium Titanite Oxide (LTO) Lithium-Ion battery with nine PEMFCs. Graphical abstract: Highlights: Integrating the fuel cell and battery technologies to provide power for a ferry. Presenting twenty-five different scenarios using a quasi-static model. System optimization using a novel parameter called PCFB. Presenting the dynamic responses to compare the stand-alone and integrated systems.